Wheel Conversation Game in Teaching Speaking Skill for EFL Classroom - Fua'di, Muhammad Musa'id (VELES Voices of English Language Education Society, 2017)
In this study the researcher investigated the effectiveness of wheel conversation game in teaching students’ speaking skill. The researcher used a pre-experimental design. The researcher used a speaking test in the form of a questioning and answering, it was given to 29 students of MA. Mu’allimat NW Pancor. The researcher calculated the mean score and standard deviation, normality, homogeneity and testing hypothesis. The results of the data analysis indicated that the mean score of pre-test was 30.48 and the post-test was 52.41. In testing hypothesis the researcher used Paired Sample t-test and total score 20.29 at p = 0.00. In normality testing the researcher used Shapiro-Wilk, total score of pre-test was 0.08 and post-test was 0.27. The result of homogeneity testing was 0.74. In this case, present researcher used One-Way Annova to look for the homogeneity testing. So null hypothesis was rejected and alternative hypothesis was accepted. Based on the data above, it can be concluded that wheel conversation game was significantly effective in teaching speaking at an EFL classroom.